Comparison of growth, relative abundance, and diet of three sympatric Hemiandrus ground wētā (Orthoptera, Anostostomatidae) in a New Zealand Forest - Nyasha Chikwature; Mary Morgan-Richards; Jessica Vereijssen; Steven A. Trewick (Journal of Orthoptera Research)
Ecology is an essential discipline for understanding the biology and behavior of organisms. This study increased knowledge of three sympatric species of ground wētā (Hemiandrus spp.). Hemiandrus ground wētā are nocturnal Ensifera that live in burrows during the day, and for these reasons, there is limited knowledge of their activity, development, and diet. We examined the diet of Hemiandrus electra, Hemiandrus ‘disparalis’, and Hemiandrus nox by examining the crop contents of specimens caught in malaise traps set in a native forest (St Arnaud) over seven months during two spring-summer-autumn seasons (2004/2005 and 2005/2006). The three species investigated varied in the plant and invertebrate fragment proportions in their diets. Hemiandrus electra and H. ‘disparalis’ were predominantly herbivores, while H. nox was primarily carnivorous, although plant matter constituted 20% of its diet. We identified the species and sex of 966 Hemiandrus wētā that were intercepted by the same malaise traps. Our results showed that H. electra was the most abundant species, with 701 individuals, while 157 and 109 were identified as H. ‘disparalis’ and H. nox, respectively. Surprisingly, the species with maternal care (H. electra) was the only one of the three sympatric Hemiandrus to have an even sex ratio; for the other two species, more males were caught in the traps. Using hind leg dimensions, we categorized each female H. electra specimen using naïve Gaussian mixture model clustering, which identified five size clusters (putatively corresponding to instars). Based on the month of collection and the growth category, we observed no seasonality in the development of this species of ground wētā, as almost all instars were found in each month of the sampling period. This study found no evidence that these nocturnal forest species synchronize their growth or reproduction with seasons.